Long-Term Comparison of Aesthetical Outcomes After Oncoplastic Surgery and Lumpectomy in Breast Cancer Patients - Santos, Gabriela; Urban, Cicero; Edelweiss, Maria Isabel; Zucca-Matthes, Gustavo [UNESP]; de Oliveira, Vilmar Marques; Arana, Gabriel Hubner; Iera, Marco; Rietjens, Mario; de Lima, Rubens Silveira; Spautz, Cleverton; Kuroda, Flávia; Anselmi, Karina; et al. (Springer Nature, 2015)
Background: Lumpectomy may result in major deformities and asymmetries in approximately one-third of patients. Although oncoplastic surgery (OP) could be a useful alternative to avoid them, lack of strong data is causing some debate. The purpose of this study was to compare aesthetic outcomes in patients undergoing OP versus lumpectomy using three different assessment methods. Methods: A total of 122 patients were included in this cross-sectional multicentric study; 57 underwent OP (46.7 %), and 65 underwent lumpectomy (53.3 %). Two breast surgeons and two plastic surgeons from different institutions using the Garbay scale independently evaluated aesthetic outcomes. BCCT.core software was applied in both groups, and the patients evaluated their aesthetic outcomes answering a questionnaire about their satisfaction rate. Results: OP group had a higher proportion of excellent aesthetic results according to the BCCT.core software analysis (p = 0.028) and the specialists (p = 0.002). Multifactorial analyses showed that age ≥70 years (RP = 6.02; 95 % confidence interval [CI] 1.73–21.0; p = 0.005), tumors in the medial, inferior, and central quadrants (RP = 4.21; 95 % CI 1.88–9.44; p < 0.001), and large breasts (RP = 7.55; 95 % CI 2.48–23.0; p < 0.001) were significant risk factors for poor aesthetic outcomes after lumpectomy. The patients classified their results as better than those by the specialists and by the software, with no statistical difference between the groups. Conclusions: Excellent aesthetic results were more frequent in the OP group according to BCCT.core software analysis and specialists. In addition, some clinical conditions and tumor locations in the breast can be considered risky factors for poor aesthetic outcomes in lumpectomy.